Biographical construction of the pedagogical knowledge of a Venezuelan migrant teacher in Boyacá - Argüello Parra, Jaime Andrés (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is the result of a research work focused on the biographical construction of the pedagogical knowledge of Narvelis Rondón, a Venezuelan migrant teacher in Boyacá, in the framework of the current socioeconomic crisis in Venezuela. The methodology consisted in a narrative exercise that aimed to reconstruct the trajectory of the migrant teacher through biographical interviews and a workshop to share memories. The guidelines for conducting the biographical narrative focused on four main areas: emergence of the teaching vocation and professional training process; development of the teaching career; the experience of migration; and reinvention of everyday life. Within the results, the pedagogical knowledge is structured in two big blocks of meaning. The first covers the experiential relationship with knowledge, including ethical training; practical teacher training, critical sense in political action, and cultural transformation as a perspective of return. The second one comprises the migratory knowledge itself based on the rooting and uprooting dialectic with impact on the different human dimensions of a teacher with a unique expression of regressive social mobility; characteristic of South-South migration. In conclusion, migration highlights the role of the teacher as a social construct and as a cultural subject. This vision contributes to understanding human transformations through the transaction of experiences and identities that influence a new nation story from the articulation of pedagogy and a biographical perspective.